Nganyareh Kabin Practices in Jukong Village: A Phenomenological Theory Perspective from Alfred Schutz (Case Study in Jukong Village, Labang District, Bangkalan Regency) - Famirotul Lail; Umi Sumbulah; Badruddin (al-Afkar, Journal For Islamic Studies, 2025)
This study analyzes the practice of Nganyareh Kabin a local term in Jukong Village, Labang District, Bangkalan Regency, for the renewal of a marriage contract, or Tajdid an-Nikah performed by married couples in a legally valid marriage. This study uses a qualitative approach with Alfred Schutz's Phenomenological theoretical framework to understand the subjective meaning of this social act from the perspective of the participants. In practice, Nganyareh Kabin is conducted very simply, privately, and secretly, without a wedding reception or crowd, attended only by the husband, wife, guardian, witnesses, and religious figures (kiai or modin). Despite its private nature, this process ensures the fulfillment of all the pillars and requirements of Islamic law, emphasizing the couple's careful attitude (ihtiyath) to ensure the legitimacy of their renewed bond. The main findings indicate that the participants' motivations are divided into two phenomenological dimensions: the "because motive" and the "in-order-to" motive. Motives stem from past experiences, such as fear of pronouncing divorce due to a major argument, lack of harmony, or financial hardship. Meanwhile, the motives stem from hopes for the future, namely to obtain blessings, recreate a family that is peaceful, loving, and compassionate, ensure a smooth flow of sustenance, and strive for offspring. From Schutz's Phenomenology perspective, Nganyareh Kabin is legitimized by a collective stock of knowledge and intersubjectively accepted within the lifeworld of the Jukong community. This practice serves as a social and spiritual adaptive mechanism that provides inner peace, is recognized by custom (‘urf sahih) and provides benefits (Maslahah Mursalah), despite being outside the framework of positive state law.